Faktor-Faktor Yang Mempengaruhi Kualitas Tutorial Program S1 PGSD Fakultas Keguruan dan Ilmu Pendidikan Universitas Terbuka - Prayekti Prayekti; Gusti Nurdin (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
This article was written based on the research results on factors influencing the quality of tutorials activities of the S1 PGDS Program implemented by the learning groups in Pangkal Pinang regional office. These factors include: 1) preparation tutorials; 2) implementation of the tutorial; 3) interaction of the tutorial classes. The analysis showed that: preparation of tutors: (a) close proximity to a tutorial site, the average value of readiness tutor 4.65 value of 4.74 and tutor activities; value 4.32 while the value of readiness tutor 4.63; tutor activity value 4.58; value of 4.03 students in tutorials; and activities of the manager with a value of 4.67; (b) medium-range, the value of readiness tutors activity value of 4.48 and 4.42,l value of 4.15 student activity, where as the value of management activities 4.34; (c) distance, the value of the student activities management for 4.56; 2) implementation of tutorials , active student learning during the tutorial with a good category for 87.5 % and 12.5 % fairly category, so the average tutor activity; 3) interaction of the tutorial classes, tutors in the implementation of the tutorial activities attract enough students, tutors while walking around the class asking students difficulty understanding when self-learning modules. In addition, to motivate students to study harder, read and understand the module more.Â ABSTRAKArtikel ini ditulis berdasarkan hasil penelitian tentang faktor-faktor yang mempengaruhi kualitas tutorial Program S1 PGSD di UPBJJ-UT Pangkal Pinang. Faktor-faktor tersebut meliputi: 1) persiapan tutorial; 2) pelaksanaan tutorial; dan 3) interaksi kelas tutorial. Hasil analisis menunjukkan bahwa: 1) persiapan tutor: (a) jarak dekat dengan lokasi tutorial, nilai rata-rata kesiapan tutor 4,63; nilai aktivitas tutor 4,58; nilai mahasiswa pada tutorial 4,03, dan aktivitas pengelola dengan nilai 4,67; (b) jarak sedang, nilai kesiapan tutor 4,48 dan nilai aktivitas tutor 4,42; nilai aktivitas mahasiswa 4,15; sedangkan nilai aktivitas pengelola 4,34; (c) jarak jauh, nilai kesiapan tutor 4,65 dan nilai aktivitas tutor 4,74; nilai aktivitas mahasiswa 4,32 sedangkan nilai aktivitas pengelola sebesar 4,56; 2) pelaksanaan tutorial, keaktifan belajar mahasiswa selama mengikuti tutorial dengan kategori baik sebesar 87,5 % dan kategori cukup sebesar 12,5 %, sehingga aktivitas tutor rata-rata baik; 3) interaksi kelas tutorial, aktivitas tutor dalam pelaksanaan tutorial cukup menarik perhatian mahasiswa, tutor berjalan berkeliling kelas sambil menanyakan kesulitan mahasiswa dalam memahami modul saat belajar mandiri. Di samping itu, memotivasi mahasiswa agar lebih giat belajar, membaca dan memahami modul.